Counter-intuitive collapse of single-layer reticulated domes subject to interior blast loading - Ma, Jialu; Fan, Feng; Wu, Chengqing; Zhi, Xudong (Thin-walled structures, 2015)
A commercial finite element package, LS-DYNA, was employed to simulate the response of a single-layer reticulated dome to an interior blast. The dome, which was initially stressed by static preloading, encountered an interesting phenomenon namely counter-intuitive collapse, which was found during the blast analysis. The Johnson–Cook constitutive model for mild steel was used to identify different failure modes of the dome for more than 2430 samples. A seemingly counter-intuitive collapse was identified due to dynamic instability. This unusual collapse was explained using total potential curves, and the critical blast load was defined. The effect of different static preloads, which is the other determination factor of counter-intuitive collapse, was investigated. A relationship between collapse and static/dynamic loads was also obtained. The results indicate that single-layer reticulated domes, with large initial stresses, may collapse at lower dynamic loads than expected. •Reasonable method for reticulated dome subject to interior blast loading.•Four failure modes were identified, counter-intuitive collapses was explained.•Relationships between collapse and static/dynamic loading were analysed.•Response zones were formed for blast-resistant design.